PENINGKATAN KARAKTER ANAK DIDIK MELALUI OPTIMALISASI KURIKULUM TPQ AL-IKHLAS DUSUN KEMPUL MENOREH SALAMAN - M. Ulin Nuha; Zaenal Abidin; Muhamad Sholikhun (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
This article discusses efforts to enhance student character through curriculum optimization at TPQ Al-Ikhlas in Kempul Hamlet, Menoreh, Salaman. The community service methodology utilized includes structured education, training, and counseling. The activities were conducted by the service team using a participatory and enjoyable approach, targeting the strengthening of children's religious and moral values. Five main aspects were the focus of the activities: tajwid learning, habituation of worship, interactive approaches, religious short sermons (kultum), and khataman appreciation activities. The results demonstrated that a proper and integrated curriculum approach could significantly increase children's discipline, responsibility, and worship competence. Supported by the local community and teachers, the program showed high effectiveness in shaping the character of the TPQ students. This research is expected to serve as a reference for developing character education models based on religious institutions like TPQ.